Hadist tentang Masa dan Rentang waktu dalam pendidikan - saiful bahri (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2021)
The concept of fitrah is a potential innate for humans that can be actualized through their environment and an educational process that can shape personality and spiritual values for children. Understand that family is the starting door for children in facing various dynamics of children's life later. Besides that regarding the hadith commandments to pray, of course we understand that children aged 7 years old can already order to do various activities, in the text of the hadith only explains to pray, but further than that we must understand contextually that it is not only prayer that is ordered, but also fasting and other sciences, this is so that children get used to him doing it when he turns 10 years old and until he is an adult. actually education or studying is unlimited means for life, as long as we are able and able to continue to study and practice and give to others as caliphs on this earth, in the process of our education as servants of Allah will continue continuously to demand and study it, and is not limited by time, distance and period like formal education has developed so far. however, it needs to be emphasized here that it is a necessity for the role of parents to play an active role in the family in the process of fostering, character building and others for children as the initial foundation in receiving knowledge and its development